PENGEJAWANTAHAN NILAI-NILAI DALAM PENGEMBANGAN BUDAYA GOTONG ROYONG DI ERA DIGITAL - Khasanah, Nur (e-Journal STAI Muhammadiyah Tulungagung, 2013)
Culture of mutual aid is part of the social capital (social capital) who once practiced by the Indonesian people, ranging from the empire, colonialism, and the beginning of freedom to realize our goals. Mutual cooperation in the context of a mutual assistance are helping each other and community service, there are two forms of consciousness and / or coercion. Lately due to various factors impact the culture, strategy development, and the lack of good examples of cultural leaders is increasingly reduced. While on the other hand, the challenges of the Indonesian nation is not getting lighter, therefore the embodiment of efforts to revitalize or societal values in the development of a culture of mutual aid is urgent and appropriate choice.